Barn blind eaudiobook - Smiley, Jane (Recorded Books Inc., 1998)
Best-selling author and Pulitzer-Prize winner Jane Smiley crafts compelling novels filled with quiet strength and emotion. In Barn Blind she portrays a middle-aged woman so galvanized with success that she drives a wedge between herself and those who love her most. Kate Karlson's only focus in life is her Midwestern horse farm. Ignoring her husband, she spends long days giving riding lessons and training horses. To showcase her teaching ability, she enters her three sons and daughter in all the equestrian shows. But when her family dares to thwart her interests, the results bring tragedy and devastation. In this spellbinding tale of love, work, and duty, Jane Smiley examines the excesses we sometimes commit in the name of ambition. Narrator Suzanne Toren's dramatic performance highlights the daily rigors and joys of the equestrian life.